PEMANFAATAN MEDIA FLASHCARD DALAM PEMBELAJARAN PENGENALAN HURUF ANAK USIA 4-5 TAHUN DI TK KANIGARAN KOTA PROBOLINGGO - Qiqek Dwi Syafitrianingrum; Benny Prasetiya (STKIP Subang, 2025)
This study explores the utilization of flashcard media in teaching letter recognition to Group A children at TK Kanigaran, Probolinggo City. A qualitative descriptive approach was employed to understand teachers' and children's experiences, teaching strategies, and responses to flashcard use. Participants included one Group A classroom (n=16s), two classroom teachers, and the school principal; data were collected through eight sessions of participant observation, semi-structured interviews with teachers and the principal, and documentation of teaching materials and children's work. Data analysis followed reduction, display, and verification procedures to generate primary themes. Findings revealed three central themes: (1) interactive teaching strategies that combine play and songs enhanced children's engagement; (2) pictorial and locally contextualized flashcard design facilitated letter-image association; and (3) implementation challenges included limited instructional time, variation in children's abilities, and the need for teacher training. The findings highlight flashcards' role as a supportive tool for early literacy through multimodal repetition and emotional engagement. Trustworthiness was ensured via data triangulation, member checking, and an audit trail. Practical implications include recommendations for inclusive flashcard design, integration of play-based activities, and teacher capacity building. This study contributes empirical evidence to early childhood education literature in Indonesia by emphasizing process, media design, and pedagogical practice within local contexts, and provides a basis for future longitudinal studies measuring early literacy development quantitatively.